2015
DOI: 10.3109/13561820.2015.1041585
|View full text |Cite
|
Sign up to set email alerts
|

A novel interprofessional approach to end-of-life care education: A pilot study

Abstract: Navigating the biomedical, emotional, and logistical complexity of end-of-life (EOL) care requires seamless interprofessional teamwork. Unfortunately, EOL care, interprofessional collaboration, and the role of support services such as hospice are not adequately emphasized in nursing and medical curricula. This article describes a student-run program, entitled the "HeArt of Medicine", which was designed to foster a reflective and collaborative approach to EOL care. The program consists of three workshops with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…The findings demonstrated that there was increased knowledge, comfort, and collaboration in EOL settings. 20…”
Section: Interprofessional Collaborative Practice As a Model For Acpmentioning
confidence: 99%
“…The findings demonstrated that there was increased knowledge, comfort, and collaboration in EOL settings. 20…”
Section: Interprofessional Collaborative Practice As a Model For Acpmentioning
confidence: 99%
“…The final sample of 34 articles contained quantitative (n ¼ 24), [9][10][11][12][13][16][17][18][19]21,23,24,[26][27][28][29][30][31][33][34][35][36]40,41 mixed methods (n ¼ 8), 14,15,20,32,[37][38][39]42 and qualitative (n ¼ 2) 22,25 studies, of which few examined interprofessional samples (n ¼ 4). [9][10][11][12] Within the studies with interprofessional samples, 3 utilized educational interventions for medical and nursing students. The other interprofessional study incorporated prelicensure medical students with licensed professionals from nursing, medicine, physiotherapy, and psychology.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…[9][10][11] For example, Korzeniewska-Eksterowicz et al 10 had almost 6 times as many medical students as nursing students in their interprofessional sample. In the study by Sinha et al, 12 researchers included medical students, prelicensure nursing students, and graduate nursing students. This study failed to distinguish between prelicensure and graduate nursing student results; therefore, only the results for medical students were included in the review table.…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations